The Mythological Basis of the Character of Ismil in the Epic "Sasna Tsrer" - Gharibyan ,Alina (Bulletin of Yerevan University B: Philology, 2026)
"Sasna Tsrer" is the only female heroine of the epic, who acts in different functions in both the second and third branches of the novel: in one case as the wife of the Great Melik, in the other as the mother of the Little Melik, which is due to the dual nature of the character. Ismil’s character is not rich in terms of motives, but she has a fateful role in the lives of the Sasna heroes. She not only becomes a wife and mother for the Sasna heroes, but also becomes an important counterweight, thanks to which the plot develops with amazing anti-drama harmony. Ismil, like Deghdzun and Khandut, makes a choice for herself as to whom to surrender to, who should give her a son. In the second branch of the novel, Ismil Khatun retains the power characteristic of the queen, the Great Mother. In this regard, in the novel outline of the second branch, Ismil becomes an equal and counterbalancing figure to the image of the wife of the Great Mher or Armaghan. In the third branch of the epic, the image of Ismil in its nature approaches the characteristics of the mother of the twin brothers, which is the second important characteristic of her in the novel.